Active procedures to control the flow past the Ahmed body with a 25° rear window. (1st January 2011) - Bruneau, Charles-Henri; Creusé, Emmanuel; Depeyras, Delphine; Gilliéron, Patrick; Mortazavi, Iraj
Ahmed body with a 25° rear window is used to represent a simplified car geometry. Two- and three-dimensional simulations are performed to analyse the flow behaviour around such a vehicle. Sucking and blowing jets or slots are added on the body to control the flow. The results presented show that good drag reductions are achieved for a good choice of the active procedure.